Antagonist coactivation analysis during Stand to Sit in post-stroke subjects - Vasconcelos, Ana Beatriz de Almeida e (2021)
After stroke, changes in antagonista coactivation are frequente, which can affect the performance of functinal tasks such as Stand to Sit (StandTS). Explore the changes in the antagonista coactivation ratio of muscle pairs of proximal and distal segments, between ipsilesional and contralesional limbs, and between StandTS subfases in post-stroke subjects. Cross-sectional observational study with 18 post-stroke subjects. Elesctromyographic activity of the rectus femoris, biceps femoris, tibialis anterior, gastrocnemius medialis and soleus was collected bilaterally, durins StandTS. Antagonist coactivation ratio was calculated in muscle pairs of both limbs for each subphase, whose subfases (stop standing, eccentric control, stabilization) dividion was based on force plate data. Between limbs, only the TA/GM muscle pair showed statistically significant diferences. Betwen the initial subphase “stop standing” and the subfases “eccentric control”there were statistically significant diferences in the TA/GM and TA/SOL musle pairs, as well as RF/BF but only the ipsilesional side. Between muscle pairs, significant diferences were revealed, only on the IPSI side, with the RF/BF pair showing greater coactivation in the “eccentric control” subfase. The antagonista coactivation levels seems change between subfases nd between muscle pairs during Stand to Sit, with no great diferences between limbs.